HUBUNGAN SERVICE RECOVERY DENGAN LOYALITAS NASABAH PADA BANK BENGKULU UNIT PANORAMA - Siti Hanila; Meimon Putra Abela (Universitas Prof. Dr. Hazairin SH, 2020)
Service recovery is a significant determinant of customer satisfaction and loyalty. The effort tomaintain a relational relationship with dissatisfied customers through effective service recoveryhas become the main focus of customer retention strategies. The purpose of this study is to findout the relationship between service recovery and customer loyalty at the Bengkulu UnitPanorama Bank. The samples in this study were 80 customers who received services from theBank Bengkulu Panorama Unit and the sampling technique was accidental sampling technique.The data collection method used quesionary and the analyst method used was Spearman rankcorrelation and data truth testing with t test